2016
DOI: 10.3390/cancers8120110
|View full text |Cite
|
Sign up to set email alerts
|

Biology, Therapy and Implications of Tumor Exosomes in the Progression of Melanoma

Abstract: Cancer is the second leading cause of death in the United States, and about 6% of the estimated cancer diagnoses this year will be melanoma cases. Melanomas are derived from transformation of the pigment producing cells of the skin, melanocytes. Early stage melanoma is usually curable by surgical resection, but late stage or subsequent secondary metastatic tumors are treated with some success with chemotherapies, radiation and/or immunotherapies. Most cancer patients die from metastatic disease, which is espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 114 publications
(170 reference statements)
0
51
0
1
Order By: Relevance
“…In melanoma, EVs, such as exosomes and microvesicles, have been reported to play a predominant role in promoting pre-metastatic niche formation, proliferation, and metastasis [ 16 ]. For example, Dror et al (2016) reported that melanosomal miR-211, which is secreted by melanoma cells and absorbed by fibroblasts, can activate the mitogen-activated protein kinase (MAPK) signaling pathway and induce fibroblast reprogramming into CAFs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, EVs, such as exosomes and microvesicles, have been reported to play a predominant role in promoting pre-metastatic niche formation, proliferation, and metastasis [ 16 ]. For example, Dror et al (2016) reported that melanosomal miR-211, which is secreted by melanoma cells and absorbed by fibroblasts, can activate the mitogen-activated protein kinase (MAPK) signaling pathway and induce fibroblast reprogramming into CAFs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… Metastasis [ 147 ] miR-135b Multiple myeloma cells endothelial cells FIH-1 Exosomal miR-135b from HR-MM cells enhances endothelial tube formation under hypoxic conditions via the HIF-FIH signaling pathway. Metastasis, angiogenesis [ 148 ] Others Melanoma miR-125b PLX4032-resistant melanoma cell line Primary melanoma cell lines apoptotic pathways miRNA inhibitors increased the fraction of apoptotic cells in LM16-R cells Metastasis [ 149 ] miR-31, − 185, and -34b A375 and SK-MEL-28 Normal melanocytes HAPLN1, GRP78 / Metastasis [ 150 ] miR-222 Metastatic melanoma cell lines Primary melanoma cell lines p27Kip1 Activates the PI3K/AKT pathway. Metastasis [ 151 ] Merkel Cell Carcinoma (MCC) miR-30a, miR-34, miR-142-3p, miR-1539 MCV-positive or -negative tumors / / Upregulation when discriminating between MCPyV-negative and MCPyV-positive MCCs MCPyV infection [ 63 , 152 ] miR-181d Downregulation when discriminating between MCPyV-negative and MCPyV-positive MCCs …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, exosomes (Exo) are nano-sized EVs that have been largely investigated in melanoma [4]. Exosomes show the ability to drive a number of specialized functions implicated in the control of proliferation, epithelial-mesenchymal transition (EMT), immune-evasion, and pre-metastatic niche formation [5,6].…”
Section: Introductionmentioning
confidence: 99%